A systematic review of the anxiety-attention relationship in far-aiming skills. Issue 1 (1st January 2019) - Payne, K. L.; Wilson, M. R.; Vine, S. J.
ABSTRACT: Theoretical accounts of the anxiety and motor performance relationship cite disruptions to attention as a critical mediating factor. The aims of this paper were to (1) systematically review published research examining attentional mechanisms underpinning the anxiety–performance relationship in targeting skills, and (2) subsequently discuss these findings in relation to contemporary theoretical perspectives. Adhering to PRISMA guidelines, three electronic databases (PubMed, PsycInfo, and SPORTDiscus) were searched from inception until June 2017. Thirty-four articles satisfied the inclusion criteria. Overall, the research is of high methodological quality; however, there is a tendency to focus on the historical dichotomy between self-focus and distraction accounts, whereas empirical support for more contemporary theoretical perspectives is lacking. Whilst this review provides further support for the role of attentional disruptions in anxiety-induced performance degradation, the exact mechanisms still lack consensus. In addition, more innovative experimental designs and measures are required to progress our understanding of moderating variables.